FORMING STUDENTS RELATIONSHIP WITH NATURE - Safarova, R. G (ANTIS PUBLISHER, 2025)
Objective: This study aims to explore the impact of nature-based educational programs on students’ environmental awareness, emotional connection to nature, and pro-environmental behavior, addressing the growing disconnect between youth and the natural environment in formal education systems. Method: A mixed-methods approach was employed, combining surveys and participatory observation of middle and high school students engaged in a semester-long outdoor immersion curriculum. Results: The findings indicate a significant enhancement in students' ecological awareness, emotional attachment to nature, and motivation to participate in environmentally responsible actions. Experiential learning and structured reflection activities were identified as key components in fostering these outcomes. Novelty: This research contributes to the field of environmental pedagogy by providing empirical evidence on the effectiveness of direct, sustained interaction with natural environments within educational contexts. It offers practical implications for curriculum development and educational policy by demonstrating how immersive, nature-based learning experiences can cultivate environmental stewardship among students.